2019
DOI: 10.1128/mra.00399-19
|View full text |Cite
|
Sign up to set email alerts
|

Genome Sequences of Six Cluster N Mycobacteriophages, Kevin1, Nenae, Parmesanjohn, ShrimpFriedEgg, Smurph, and SpongeBob, Isolated on Mycobacterium smegmatis mc 2 155

Abstract: The annotation of six cluster N Mycobacterium smegmatis phages (Kevin1, Nenae, Parmesanjohn, ShrimpFriedEgg, Smurph, and SpongeBob) reveals regions of genomic diversity, particularly within the central region of the genome. The genome of Kevin1 includes two orphams (genes with no similarity to other phage genes), with one predicted to encode an AAA-ATPase.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 11 publications
0
9
0
Order By: Relevance
“…Phages (GenBank accession numbers KC576783 [Butters], HM152765 [Island3], and MN945904 [Eponine]) were isolated and grown on Mycobacterium smegmatis mc 2 155 as described in (Caratenuto et al . 2019) Island3 lysate was obtained from the Hatfull lab (University of Pittsburgh).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Phages (GenBank accession numbers KC576783 [Butters], HM152765 [Island3], and MN945904 [Eponine]) were isolated and grown on Mycobacterium smegmatis mc 2 155 as described in (Caratenuto et al . 2019) Island3 lysate was obtained from the Hatfull lab (University of Pittsburgh).…”
Section: Methodsmentioning
confidence: 99%
“…) were isolated and grown on Mycobacterium smegmatis mc 2 155 as described in (Caratenuto et al 2019) Island3 lysate was obtained from the Hatfull lab (University of Pittsburgh). The genomic sequence for the Island3 strain used in this study differs from that of the wild type with a 257bp deletion (coordinates 43307 to 43563) and a C2656T SNP.…”
Section: Phage Isolation Propagation and Genomic Analysis Phages (Gen...mentioning
confidence: 99%
“…Due to the intracellular nature of M. tuberculosis , phage access to the bacterium is difficult. However, using carriers such as M. smegmatis and phage encapsulation [ 55 58 ], the phage can be transported and reach the bacteria. Another challenge with mycobacteriophage therapy is phage resistance.…”
Section: Challenges Of Using Mycobacteriophages In the Treatment Of T...mentioning
confidence: 99%
“…There are several general phage features that make mycobacteriophages suitable as therapeutic agents against drug-resistant TB [ 132 , 141 ]: (a) By nature, phages only infect and replicate inside their bacterial hosts without harming the human eukaryotic cells, and have the capacity to lyse and kill their hosts at the infection site [ 142 ]; (b) Their host range is mostly limited to Mycobacterium spp., which allows for the development of targeted therapies for specific M. tuberculosis strains with no apparent collateral damage to the human microbiota [ 143 ], representing one of the major advantages of phage therapy over the use of drugs; (c) Phages are the most abundant organisms in the biosphere (10 31 viral particles estimated for the entire phage population [ 144 , 145 ]), isolated from multiple environments through common and well-established microbiology techniques [ 91 ], and easy to characterize using molecular biology tools [ 146 ]. New mycobacteriophages have been sequenced and characterized these past few years [ 73 ], indicating the existence of a great phage diversity [ 147 ], which could lead to the discovery of novel mechanisms to disrupt the M. tuberculosis cell envelope; (d) Phages are easy to engineer to contain suitable features for phage therapy; (e) Because phages have the ability to replicate inside the pathogen using the bacterial cell machinery to generate more viral particles, less number of doses are required when compared to drug treatments [ 143 ]. In this context, mathematical model for population dynamics showed that a single dose of phages is more effective than multiple doses of drugs to treat systemic infections caused by E. coli [ 148 ]; and lastly (f) Phages are easy to propagate at large-scale in an in vitro setting, significantly reducing the production costs when compared to drugs [ 132 ].…”
Section: Phage Therapy To Treat Multidrug-resistant Tbmentioning
confidence: 99%
“…On the other hand, it also represents a significant limitation, as this high specificity might create a bottleneck in terms of identifying potential phage candidates to efficiently kill M. tuberculosis . However the growing mycobacteriophage database [ 72 ] is proof that newly isolated mycobacteriophages are being sequenced and characterized frequently, showing a great degree of genome diversity that could potentially expand the host range possibilities of the existing phage pool [ 92 , 147 ]. Indeed, mycobacteriophages have the ability to switch or expand their host range frequently among different mycobacterial strains [ 77 , 156 ].…”
Section: Phage Therapy To Treat Multidrug-resistant Tbmentioning
confidence: 99%